The current-voltage characteristics of FSS/n-Si heterojunction diode under dark and illumination - Yakuphanoğlu, Fahrettin (Elsevier Science Bv, 2007)
The current-voltage characteristics of the organic/inorganic fluorescein sodium salt FSS/n-Si heterojunction diode under dark and illumination have been investigated. The diode parameters such as barrier height and ideality factor were determined. The ideality factor n value at different temperatures was found to be in range from 6.30 to 4.56. These values suggest that the FSS/n-Si heterojunction diode is a non-ideal contact. A space charge limited-conduction (SCLC) mechanism, where current increases superlinearly, i.e, I proportional to V-m > 2, takes place in the diode. The photocurrent properties of the diode under various illuminations have been investigated. The photocurrent in the reverse direction is strongly increased by photo-illumination. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: heterojunction diode; space charge limited conduction; photocurrent